ANALYSIS OF RISK ASPECTS OF GOLD MORTGAGE PRODUCTS - scholastika scholastika; kamaluddin ritonga; hamni fadilah; rahmat annam (Institut Agama Islam Negeri Padangsidimpuan, 2021)
This research is motivated by the analysis of the risk aspects of gold pawn products at PT. Pegadaian (Persero) Sibuhuan Syari'ah Service Unit. The types of gold and the varying price of gold in the market pose risks. The decline in gold prices will result in losses during the auction for PT. Pegadaian (Persero) Sibuhuan Syari'ah Service Unit. Pegadaian is more careful in following the price developments in the market, as well as the types of gold that supervises, must be more careful and thorough in assessing goods. What are the risks that occur in gold pawn products at PT. Pegadaian (Persero) Sibuhuan Sharia Service Unit. How are the steps to minimize the risk of products that are pawning gold. The purpose of this research is to see the risk of gold pawn products. The theory presented in this study is related to shari'ah pawnshops, the theory of gold pawn risk, the theory of economic uncertainty, natural uncertainty, human uncertainty. This research is a qualitative research with descriptive method. The data source used is primary data and secondary data. While the technique, the data of this research are interviews, observation and documentation. The results of the research on the Analysis of the Risk Aspects of Gold Pawn Products that occurred at PT. Pegadaian (Persero) Syari'ah Sibuhuan Service Unit is a market risk, namely a decrease in the price of gold which results in losses at the time of the auction, credit risk, namely the risk caused by the inability of the customer to pay off its obligations, operational risk, namely the risk arising from inadequacy in the management process. such as the entry of counterfeit gold, negligence in appraising collateral, legal risk of criminal acts either robbery or employee fraud, reputation risk, namely due to customer complaints against products or services at PT. Pegadaian (Persero) Syari'ah Sibuhuan Service Unit and natural disasters (force majeure), namely risks that cause losses with catastrophic disasters. The steps taken by PT. Pegadaian (Persero) Syari'ah Sibuhuan Service Unit to minimize the risk of gold pawn product risk by conducting supervision, guidance and supervision. Education is carried out for appraisers to update knowledge and refresh the existing estimators in the pawnshop.